2013
DOI: 10.1016/j.plipres.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of brain fatty acid-binding protein with the polyunsaturated fatty acid environment as a potential determinant of poor prognosis in malignant glioma

Abstract: Malignant gliomas are the most common adult brain cancers. In spite of aggressive treatment, recurrence occurs in the great majority of patients and is invariably fatal. Polyunsaturated fatty acids are abundant in brain, particularly ω-6 arachidonic acid (AA) and ω-3 docosahexaenoic acid (DHA). Although the levels of ω-6 and ω-3 polyunsaturated fatty acids are tightly regulated in brain, the ω-6:ω-3 ratio is dramatically increased in malignant glioma, suggesting deregulation of fundamental lipid homeostasis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 122 publications
0
53
0
Order By: Relevance
“…Hence, although there is available evidence suggesting that DHA as a natural ligand of PPAR influences the FABP7 expression (Elsherbiny et al . ), the novelty of our study lies in appraising their link and thoroughly validating the mechanism of FABP7 and PPARγ interactions. We also related these findings to PI3K/AKT that played a pivotal regulatory role in the present investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, although there is available evidence suggesting that DHA as a natural ligand of PPAR influences the FABP7 expression (Elsherbiny et al . ), the novelty of our study lies in appraising their link and thoroughly validating the mechanism of FABP7 and PPARγ interactions. We also related these findings to PI3K/AKT that played a pivotal regulatory role in the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…; Elsherbiny et al . ). However, impact of DHA on FABP7 together with PPARγ is unexplored in the primary astrocytes.…”
mentioning
confidence: 97%
“…PUFAs are the main component of cell membrane phospholipids bilayer which play pivotal roles in maintaining membrane structure, energy provision, and cell signaling 41,42 . Of note, studies have indicated that PUFAs may be critical for cancer incidence [43][44][45] . PUFAs and its derived metabolites, coordinating signal transduction and microenvironment to accelerate tumor growth and spread.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar to the previously mentioned proteins, caution must be taken, as the studies do not have the temporal resolution to distinguish between transport and uptake secondary to changes in metabolism. Members of the FABP family facilitate the uptake of fatty acid secondary to their metabolism and are important in the trafficking of fatty acids, the regulation of eCB signaling among others, and we refer the reader to several recent reviews (Moulle et al, 2012;Elsherbiny et al, 2013;Schroeder et al, 2016). Of particular interest are recent studies on FAPB-5, which facilitates the uptake of DHA into the brain, and KO reduces brain DHA by approximately 15% and is associated with impaired working and shortterm memory (Pan et al, 2015(Pan et al, , 2016.…”
Section: B Mechanisms Of Dha Entry Into the Brainmentioning
confidence: 99%